Internet-based temperature monitoring system (IBTMS) for furnace combustion system of steel making plant - Wan Azman bin Wan Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
The behaviors of the temperature displaying system have been discussed in this thesis and have been compared to the existing system in the steel making plant in Malaysia. Temperature display can be designed in many ways. It can be displayed in LCD, seven segment display and many other types of protocol that can display the temperature. For instance, in the steel making plant that involved in this research, we have discovered that the display for the temperature have been located at the touch screen and it can be controlled in an easy mode. Therefore, this thesis will be based on the industrial features but need some amendments in order to achieve the objective of the project. The most important aspect, this temperature display can be viewed through internet connection that will give an extra credit for the user to use this application in a wider way.